Pelestarian Arsip Pemerintah Swapraja di Yogyakarta pada Masa Pemerintahan Hindia Belanda - Faizatush Sholikhah; Suhardo Suhardo (Journal of Social and Policy Issues, 2021)
Archives are recorded information in the form of media and various information characteristics. Archives are created as a result of activities in carrying out organizational functions. From these activities, transactions occur and then archives are created that can be used as authentic evidence in the implementation of social, national and state life. One of the efforts to preserve archives is by keeping the information contained in the archives can be stored and accessed and provides benefits in maintaining the nation's memory. Language is software rather than archives that are used as a communication tool, can reflect the culture and behaviour of the community in carrying out national life. In the sense that the language used in the behaviour of everyday life in society at that time, from various levels of a pluralistic society. This study discusses the government archives in Yogyakarta during the Dutch East Indies Administration, in the context of preserving the information and memories contained in the archives, it’s important to understanding the language of the text in the archives produced by the Government during the Dutch East Indies period.